2014
DOI: 10.1111/1462-2920.12674
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization of anaerobic ammonium oxidizing bacterium ‘CandidatusJettenia caeni’

Abstract: To date, six candidate genera of anaerobic ammonium-oxidizing (anammox) bacteria have been identified, and numerous studies have been conducted to understand their ecophysiology. In this study, we examined the physiological characteristics of an anammox bacterium in the genus 'Candidatus Jettenia'. Planctomycete KSU-1 was found to be a mesophilic (20-42.5°C) and neutrophilic (pH 6.5-8.5) bacterium with a maximum growth rate of 0.0020 h(-1) . Planctomycete KSU-1 cells showed typical physiological and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(95 citation statements)
references
References 124 publications
(177 reference statements)
6
87
1
1
Order By: Relevance
“…In the present study, we showed the intracellular localization of the hydroxylamine oxidoreductase (HAO)-like protein kustc0457/58, hydrazine dehydrogenase (HDH), the NO-producing HAO-like protein HOX, nitrite oxidoreductase (NXR), and hydrazine synthase (HZS) within an anammox cell. All of these proteins are encoded in all presently available anammox genomes and play key roles in anammox catabolism (1,2,(9)(10)(11)(12)(13)(14). The fact that all studied protein complexes were exclusively immunolocalized to the anammoxosome in the present study supported the hypothesis that this cell compartment was a true prokaryotic organelle with a dedicated function.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, we showed the intracellular localization of the hydroxylamine oxidoreductase (HAO)-like protein kustc0457/58, hydrazine dehydrogenase (HDH), the NO-producing HAO-like protein HOX, nitrite oxidoreductase (NXR), and hydrazine synthase (HZS) within an anammox cell. All of these proteins are encoded in all presently available anammox genomes and play key roles in anammox catabolism (1,2,(9)(10)(11)(12)(13)(14). The fact that all studied protein complexes were exclusively immunolocalized to the anammoxosome in the present study supported the hypothesis that this cell compartment was a true prokaryotic organelle with a dedicated function.…”
Section: Discussionsupporting
confidence: 81%
“…Apart from nitrite reductase, all currently available anammox genomes encode close homologs of the proteins described above (2,(9)(10)(11)(12)(13)(14), suggesting that they have the same energy metabolism as K. stuttgartiensis.…”
mentioning
confidence: 99%
“…At present, it is unclear whether the essential nitrogen transforming enzymes utilize iron or copper cofactors. Phylogenetic analysis has identified both iron and copper binding domains in the genome of annamox bacteria (Ali et al, 2015), and copper limitation of anammox activity has been observed in the field (Jacquot et al, 2013). The evolutionary history of anammox is also poorly known.…”
Section: Anaerobic Ammonium Oxidation (Anammox)mentioning
confidence: 99%
“…from Ca 'Jettenia sp. ', the characteristics of the maximum specific growth rate (µ max ) and the half-saturation constants (Ks NH4 and Ks NO2 for NH 4 + and NO 2 ‾, respectively) are compared [60]. parameters [1].…”
Section: Detection Of Anammox Bacteriamentioning
confidence: 99%